Effect of Fluridone on Roots and Leaf Buds Development in Stem Cuttings of Salix babylonica (L.) ‘Tortuosa’ and Related Metabolic and Physiological Traits - Wiesław Wiczkowski; Agnieszka Marasek-Ciołakowska; Dorota Szawara-Nowak; Wiesław Kaszubski; Justyna Góraj-Koniarska; Joanna Mitrus; Marian Saniewski; Marcin Horbowicz (Molecules)
The herbicide fluridone (1-methyl-3-phenyl-5-[3-trifluoromethyl (phenyl)]-4(1H)-pyridone) interferes with carotenoid biosynthesis in plants by inhibiting the conversion of phytoene to phytofluene. Fluridone also indirectly inhibits the biosynthesis of abscisic acid and strigolactones, and therefore, our study indirectly addresses the effect of reduced ABA on the roots and leaf buds development in stem cuttings of Salix babylonica L. ‘Tortuosa’. The stem cuttings were kept in distilled water (control) or in a solution of fluridone (10 mg/L) in natural greenhouse light and temperature conditions. During the experiments, morphological observations were carried out on developing roots and leaf buds, as well as their appearance and growth. After three weeks of continuous treatments, adventitious roots and leaf buds were collected and analysed. Identification and analysis of anthocyanins were carried out using micro-HPLC-MS/MS-TOF, while HPLC-MS/MS was used to analyse phenolic acids, flavonoids and salicinoids. The fluridone applied significantly inhibited root growth, but the number or density of roots was higher compared to the control. Contents of salicortin and salicin were several dozen times higher in leaf buds than in roots of willow. Fluridone increased the content of salicortin in roots and leaf buds and declined the level of salicin in buds. Fluridone also declined the content of most anthocyanins in roots but enhanced their content in buds, especially cyanidin glucoside, cyanidin galactoside and cyanidin rutinoside. Besides, fluridone markedly decreased the level of chlorophylls and carotenoids in the leaf buds. The results indicate that applied fluridone solution reduced root growth, caused bleaching of leaf buds, and markedly affected the content of secondary metabolites in the adventitious roots and leaf buds of S. babylonica stem cuttings. The paper presents and discusses in detail the significance of fluridone’s effects on physiological processes and secondary metabolism.